2013
DOI: 10.2298/bah1302233n
|View full text |Cite
|
Sign up to set email alerts
|

Objectives and approaches in the breeding of perennial legumes for use in temporary pasturelands

Abstract: Legumes are the major element of grassland ecosystem, on which the forage quality depends. Breeding of pasture varieties in perennial legumes firstly aims at achieving tolerance and persistence of the legume component in the pasture. In species having low natural grazing tolerance (lucerne and red clover) it is necessary to conduct breeding for biological, morphological and physiological characteristics, directly related to grazing tolerance. In the species having high grazing tolerance (white clover, birds fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Northern China not only has cold winters, but also a dry and windy climate, which causes alfalfa to suffer from a combination of cold and drought stress from winter to early spring. Previous studies have shown that favorable moisture conditions in winter are conducive to the successful overwintering of forage (Naydenova et al, 2013). W ater has a high heat capacity and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Northern China not only has cold winters, but also a dry and windy climate, which causes alfalfa to suffer from a combination of cold and drought stress from winter to early spring. Previous studies have shown that favorable moisture conditions in winter are conducive to the successful overwintering of forage (Naydenova et al, 2013). W ater has a high heat capacity and thermal conductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the morphological investigations of several T. pratense populations showed a correlation of persistency with non-favorable traits, like small plant size and prostrate growth habit [17]. Moreover, most T. pratense cultivars or accessions are locally adapted and require their specific local conditions to show the favored traits [18,19], which decreases the stability for individual traits in breeding efforts [20]. T. pratense exhibits significant intraspecific variation due to high intrapopulation genetic diversity, thus, persistence and performance in response to mowing or cutting depends on the variety as well as on the developmental stage at the moment of damage [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the morphological investigations of several T. pratense populations showed a correlation of persistency with non-favorable traits, like small plant size and prostrate growth habit [17]. Moreover, most T. pratense cultivars or accessions are locally adapted and require their speci c local conditions to show the favored traits [18,19], which decreases the stability for individual traits in breeding efforts [20]. T. pratense exhibits signi cant intraspeci c variation due to high intrapopulation genetic diversity, thus, persistence and performance in response to mowing or cutting depends on the variety as well as on the developmental stage at the moment of damage [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%